Correlation of photocatalytic activity and defects generated in Ca2+-based heterojunctions - Coleto, Ubirajara [UNESP]; Amoresi, Rafael A. C. [UNESP]; Pereira, Chrystopher A. M. [UNESP]; Schmidt, Bruna W. [UNESP]; Iani, Isabela M. [UNESP]; Simões, Alexandre Z. [UNESP]; Monteiro, Elias S. [UNESP]; Longo, Elson; Zaghete, Maria A. [UNESP]; Perazolli, Leinig A. [UNESP] (Springer Nature, 2020)
In this work a new semiconductor based on calcium heterojunction (CaO/CaTiO3) was evaluated to the optical properties correlated to crystalline lattice defects. The heterojunctions of the semiconductor were prepared by the sol–gel route and its formation was confirmed by the intimate contact interface between crystalline phases. Morphology and elemental composition of the nanometric heterojunction were evaluated. Chemical environment and composition of the surface were used to determine the oxidation state of the material constituents. The electronic structure was evaluated and the relationship among band gap energy, photoluminescent emission energy, and photocatalytic activity of the materials was demonstrated. Oxygen vacancies located on the surface promoted photoluminescent spectra emission in the green wavelength, making them more photoactive than those defects that emitted in the red region. The use of active species scavenger indicated that the photogenerated species with the greatest photocatalytic action was the superoxide radical. This study has developed calcium heterojunctions for application as photocatalysts, demonstrating the importance of the defects generated in the production of heterojunctions and the activity of photogenerated species, studied using scavengers.
Keywords: Heterojunctions; Oxygen vacancies; Photocatalysis; Scavenger; Structural defects